THE ROLE OF INTERACTIVE PLATFORMS IN LEARNING ENGLISH FOR MEDICAL STUDENTS - Norboboyeva Saida Azamatovna; Khusniddinova Yokutkhon (KLINIK TADQIQOTLAR VA INNOVATSION TIBBIYOT, 2026)
This article investigates the pedagogical effectiveness of using interactive digital platforms in learning English by medical students. Within the framework of English for Medical Purposes (EMP), interactive platforms play a vital role in developing students’ professional vocabulary, communicative competence, and learner autonomy. The study examines the application of platforms such as Moodle, Google Classroom, Quizlet, Kahoot, Padlet, and Zoom in the English language learning process. Drawing on the perspectives of prominent scholars in ESP and educational technology, the article demonstrates that interactive platforms significantly enhance students’ motivation, engagement, and overall learning outcomes in medical English education.